(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Background: Primary dysmenorrhea (PD) is one of the common medical problems among the adolescent girls and young women. According to modern medicine, PD is painful menstruation without any underlying pathologies. Whereas in TCM PD refers to menstrual pain that occurs due to blockage or deficiency of chi, heat retention, liver, and kidney imbalance, dampness of wind. Acupuncture has good impact in case of pain and hormonal problems. Hence, acupuncture can be a good choice of intervention for PD.